Analisis Framing Pemberitaan Ferdy Sambo di Media Online Viva.co.id dan Detik.com - Rahman, Rafiku (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The news of the murder of Brigadier J became exciting news in the Indonesian cyberspace in July 2022, which really colored the mass media in Indonesia. From the results of the investigation, Ferdi Sambo was named as the suspect. Previously, Ferdi Sambo said he was just a victim of abuse experienced by his wife. The media began to pay attention to this case. Among them are Viva.co.id and Detik.com. This research aims to analyze how news about Ferdy Sambo is framed in two main online media, namely Viva.co.id and Detik.com. Framing in this context refers to the way the media shapes, organizes and directs people's perceptions of an event or character. The method used is Robert N. Entman's framing analysis by paying attention to Define Problems, diagnose causes, make moral judgments and treatment recommendations. The data source used as material for analysis is news from the two media from July to November 2022. The research results show that Viva.co.id and Detik.com in framing have different approaches in presenting Ferdy Sambo news. The articles written are different but refer to the same theme, namely the Ferdy Sambo case.